COMPLEX ECOLOGICAL ASSESSMENT OF AEROINDUSTRIAL LOADING IN THE AREA OF CEMENT ENTERPRISE INFLUENCE - Valter, G.; Voronova, Ye.; Perekhrest, A.; Вальтер, Г. А.; Воронова, Е. М.; Перехрест, А. С. (Харьковский национальный автомобильно-дорожный университет, 2011)
Dynamic changes of major components of forest ecosystems in relation to distance from the plant as a loading factor on the environment are considered.
КОМПЛЕКСНАЯ ЭКОЛОГИЧЕСКАЯ ОЦЕНКА АЭРОТЕХНОГЕННОЙ НАГРУЗКИ В ЗОНЕ ВЛИЯНИЯ ЦЕМЕНТНОГО ПРОИЗВОДСТВА
КОМПЛЕКСНА ЕКОЛОГІЧНА ОЦІНКА АЕРОТЕХНОГЕННОГО НАВАНТАЖЕННЯ В ЗОНІ ВПЛИВУ ЦЕМЕНТНОГО ВИРОБНИЦТВА
Keywords: maximum permissible concentration (MPC); forest ecosystem; impact; buffer; field zone; предельно допустимая концентрация (ПДК); лесная экосистема; импактная; буферная и фоновая зона; гранично допустима концентрація (ГДК); лісова екосистема; імпактна; буферна і фонова зона; 612.863.2